LITERASI MAULID NABI DI KALANGAN ULAMA MINANGKABAU: PEMERIAN NASKAH DAN ANALISIS DINAMIKA WACANANYA - Pramono Pramono (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2015)
The article is focused on the dynamics of Maulid Nabi (MN / Birthof the Prophet Muhammad) discourses in Minangkabau manuscripts (kitabs) written by local Muslim scholars. In the context of local Islamic discourses, the MN discourse is one of the controversial polemics that encourage some scholars to conduct researches on it. However, the studies on the manuscripts written by the Minangkabau Muslim scholars arestill very rare to find. Therefore, one of the objectives of this thesis is to fill in â€œthe blankâ€ on the related literatures of MN discourse analysis in Minangkabau by studying the manuscripts of local Muslim scholars. This study use Critical Discourse Analysis (CDA) by combining the CDA model of Norman Fariclough and Ruth Wodak. In CDA perspectives, the MN discourses are not only analysed at the texts level only but also preceded at the historical and socio-cultural contexts of the texts. Generally, this study explains how the manuscripts of the local Muslim scholars describe the discourse dynamic of MN in Minangkabau. To arrive at the conclusion, the MN discourses are analysed starting from the discourses production, distribution, and consumption. From the analysis, the study shows some facts that the works discursively related to MN had become ideologicaldiscourses which shape and strengthen the identity of elderMinangkabau Muslim scholars (Kaum Tua). At the same time, the practices of MN discourses become the strong values protecting them from the discursive attack of the younger Muslim scholars (Kaum Muda). Discourses war in writing and public debate in the reformation of Islam in Minangkabau had given positive impacts on the intellectual traditions in Minangkabau scholars for both the elder and younger Muslim scholars.Â Artikel ini memfokuskan kajiannya terhadap dinamika wacanaMaulid Nabi (MN) di Minangkabau melalui naskah-naskah karya para ulama lokal. Dalam konteks dinamika Islam tempatan, wacana MN merupakan salah satu isu polemik keislaman di Minangkabau yang cukup kontroversial dan memancing beberapa sarjana untuk melakukan penelitian terhadapnya. Akan tetapi, kajian yang menggunakan naskhahnaskhah karya ulama tempatan sebagai sumber utamanya masih sedikitdilakukan. Kajian ini menggunakan teori Analisis Wacana Kritis (AWK) dengan menggabungkan model CDA Norman Fairclough dan Ruth Wodak. Dalam perspektif AWK, wacana MN tidak hanya dianalisis pada peringkat teks saja, namun diteruskan pada aspek konteks sejarah dan sosial budayanya. Secara umum, kajian ini menjelaskan sejauh mana naskhahnaskhah karya para ulama tempatan menggambarkan dinamika wacanaMN di Minangkabau. Untuk sampai pada tujuan kajian, wacana MN dianalisis mulai dari proses produksi, distribusi hingga konsumsi wacana. Dari analisis yang dilakukan, kajian ini menampilkan fakta bahwa karya sastra berkenaan dengan MN secara diskursif telah menjadi wacana yang berideologi, sehingga mampu membentuk dan memperkuat identitasKaum Tua di Minangkabau. Pada saat yang bersamaan, praktik wacana tersebut menjadi kekuatan yang tangguh untuk menyangkal serangan secara diskursif yang dilancarkan oleh kalangan ulama Kaum Muda. Perang wacanaâ€”baik melalui tulisan dan debat terbukaâ€”pada era transmisi pembaharuan Islam di Minangkabau telah memberi kesan positif terhadaptradisi intelektual dalam kalangan ulama Minangkabau.